Perception of the sexual sphere of older people by young people, taking into account ageism attitudes and the level of their own sexual satisfaction - Jarka Wencel (Edukacyjna Analiza Transakcyjna)
Postrzeganie sfery seksualnej osób starszych przez osoby młode, uwzględniając postawy ageizmowe i poziom własnej satysfakcji seksualnej